A análise da efetividade das leis 11340/06 e 13.104/15 na diminuição dos casos de violência contra o gênero feminino. - Cassucci, Victor Bonagamba [UNESP] (Universidade Estadual Paulista (Unesp), 2020)
The struggle of women in society for the claim of rights dates from 1820 and extends to the present day, with the constant search for more space in Aristotelian, prejudiced and archaic society. Having the law 11340/06, which aims to protect the female gender, completed 10 years of creation in 2016 and the Feminicide law, which provides for femicide as qualifying circumstances of the crime of homicide, which came into force in 2015, the objective of this study was to analyze the violence against women in the national territory correlating with the laws, in order to analyze if there was effectiveness and reduction of the crimes covered. This is a cross-sectional quantitative study. The collection was carried out in the database of the security secretariat, mortality information system, ministry of health, health surveillance secretariat. Descriptive statistical analyzes were performed. In the analyzed data, there is no uniformity of period as there is a lag in the statistical survey and in the integration of information. From 1980 to 2017, homicide numbers were collected at the Ministry of Health, the health surveillance secretariat and the mortality information system, where it was observed that there was a small decline in the mortality rate related to the female gender in the years of enactment of laws : 2006 and 2015; from 2005 to 2019 the data were obtained through a perception survey, carried out by DataSenado - Senado Federal, where it was pointed out an increase in the rate of women who are abused domestically; from 2011 to 2017 the data were collected at the Observatório da Mulher Contra Violência, where they pointed to a change in homicide rates, with a small interval and always an increase, in all subsequent years, in cases of notification due to health. It is concluded that even with Law 11340/06 more than ten years ago and Law 13.104 / 15, granted in 2015, the prevalence of violence against women is still high.

A luta da mulher na sociedade pela reivindicação de direitos data-se desde 1820 e se estende até os dias atuais, com a busca constante de mais espaço na sociedade aristotélica, preconceituosa e arcaica. Tendo a lei 11340/06 , que visa a proteção do gênero feminino, completado 10 anos de criação em 2016 e a lei do Feminicídio, que prevê o feminicídio como circunstancias qualificadoras do crime de homicídio, entrado em vigor em 2015, o objetivo deste estudo foi analisar a violência contra a mulher no território nacional correlacionando com as leis, para assim se analisar se houve efetividade das mesmas e diminuição dos crimes abrangidos. Trata-se de um estudo transversal descritivo quantitativo. A coleta foi realizada no banco de dados do sistema de informação de mortalidade, ministério da saúde, secretaria de vigilância em saúde, Data Senado e Observatório da Mulher Contra a violência. Realizou-se analises estatísticas descritivas. Nos dados analisados, não há uniformidade de período pois há defasagem no levanta- mento estatístico e na integração das informações. De 1980 a 2017 foram coletados os números de homicídios no Ministério da Saúde, na secretaria de vigilância em saúde e no sistema de informação de mortalidade, onde se observou que houve pequeno declino no índice de mortalidade relacionada ao gênero feminino nos anos de promulgação das leis; De 2005 a 2019 os dados foram obtidos através de uma pesquisa de percepção, realizada pelo DataSenado - Senado Federal, onde foi apontado um crescimento no índice de mulheres violentadas domesticamente; de 2011 a 2017 os dados foram coletados no Observatório da Mulher Contra a violência, onde apontaram uma alternância nos índices quanto a homicídios, com um intervalo pequeno e sempre um aumento, em todos os anos subsequentes, nos casos de notificação por conta da saúde. Conclui-se que mesmo com a instituição da Lei 11340/06 há mais de dez anos e a Lei 13.104/15, outorgada em 2015, ainda é grande a prevalência de violência contra o gênero feminino.
The analysis of the effectiveness of laws 11.340 / 06 and 13.104 / 15 in reducing cases of violence against women.
Keywords: Domestic violence; Mulheres; Violência doméstica; Homicídio